1998
DOI: 10.3141/1643-06
|View full text |Cite
|
Sign up to set email alerts
|

Project Scoping Using Falling Weight Deflectometer Testing: New Jersey Experience

Abstract: The experience of New Jersey with pavements, like that of many other states, goes back to the last century. Highways constructed early in this century are still in service. During these extensive service lives, several maintenance and rehabilitation activities were applied to keep the pavements in good condition. These activities ranged from patching to full reconstruction. Also, most of New Jersey pavements have been widened at least once. With all these factors, it is difficult to identify the limits of homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…Therefore, different decisions are taken if only functional condition parameters are employed, or if deflection tests are included in the decision process [88]. Hence, the introduction of a structural capacity index is suggested in network-level decisions to find the most cost-effective rehabilitation option [89].…”
Section: Pavement Data Collectionmentioning
confidence: 99%
“…Therefore, different decisions are taken if only functional condition parameters are employed, or if deflection tests are included in the decision process [88]. Hence, the introduction of a structural capacity index is suggested in network-level decisions to find the most cost-effective rehabilitation option [89].…”
Section: Pavement Data Collectionmentioning
confidence: 99%
“…Table 2 shows a sample of the sectioning results. A similar pavement sectioning concept was used in a previous study (3). Results of this study indicated that the rehabilitation cost would be reduced significantly if long projects were divided into structurally homogeneous sections.…”
Section: Homogeneous Sectionsmentioning
confidence: 83%
“…Asphalt pavement produces mechanical energy and heat when a vehicle passes, and the mechanical energy can be used by the piezoelectric transducer to generate electrical energy. Most of the current road health testing uses large, cumbersome ultrasonic nondestructive testing [ 47 ] or falling weight deflectometers [ 48 ], which can be very costly in terms of both manpower and resources. Most detection instruments can only detect surface damage.…”
Section: The Pavement Problem and The Pavement Sensing Systemmentioning
confidence: 99%